Traditional Media Strategies in the Age of New Media - Rizki Pratama; M. Yoserizal Saragih (LEGAL BRIEF, 2022)
This article examines how traditional media can thrive in the age of new media. Humans essentially require information, so media is required to meet basic human needs. Traditional media and new media are the two types of media. Along with the development of technology, traditional media has decreased interest so that it has the potential to become extinct. The main reasons for the decline in public interest in traditional media are public distrust and easy access to new media. This article employs a literature review method, which borrows qualitative research in order to discover new breakthroughs. The study's findings indicate that the presence of new media has begun to threaten traditional media's position, but it is possible that traditional media can compete with new media because new media theories that account for traditional media's credibility have yet to be developed. Traditional media can employ a variety of strategies, including campaigning, ensuring the accuracy of information, and fusing digitalization and traditional media.